Nicotinamide adenine dinucleotide is transported into mammalian mitochondria - Davila, Antonio; Liu, Ling; Chellappa, Karthikeyani; Redpath, Philip; Nakamaru-Ogiso, Eiko; Paolella, Lauren M; Zhang, Zhigang; Migaud, Marie E; Rabinowitz, Joshua D; Baur, Joseph A (eLife, 2018)
Mitochondrial NAD levels influence fuel selection, circadian rhythms, and cell survival under stress. It has alternately been argued that NAD in mammalian mitochondria arises from import of cytosolic nicotinamide (NAM), nicotinamide mononucleotide (NMN), or NAD itself. We provide evidence that murine and human mitochondria take up intact NAD. Isolated mitochondria preparations cannot make NAD from NAM, and while NAD is synthesized from NMN, it does not localize to the mitochondrial matrix or effectively support oxidative phosphorylation. Treating cells with nicotinamide riboside that is isotopically labeled on the nicotinamide and ribose moieties results in the appearance of doubly labeled NAD within mitochondria. Analogous experiments with doubly labeled nicotinic acid riboside (labeling cytosolic NAD without labeling NMN) demonstrate that NAD(H) is the imported species. Our results challenge the long-held view that the mitochondrial inner membrane is impermeable to pyridine nucleotides and suggest the existence of an unrecognized mammalian NAD (or NADH) transporter.
Keywords: NAD; NADH; nicotinamide; niacin; mononucleotide; mitochondria